Jesus, Socialism, and "Judeo-topia" - Hanson, Kenneth L. (Socio-historical examination of religion and ministry, 2023)
This article addresses the contention commonly expressed among liberal theologians and commentators that the Jesus of history, to the extent that he may be identified, was essentially a social revolutionary, broadly sympathetic to what might be identified in contemporary terms as ideological "socialism." It is often conceived that Jesus’ concern for the poor, the disenfranchised, and the underclass of Second Temple Judea endows him with a broad egalitarian ethic, making him akin to an ancient "redistributionist." I will argue, however, that "socialism" did indeed exist in those days, in the form of the Dead Sea sect, and that the historical Jesus was profoundly opposed to the community of property it represented. For him, "social justice" was part of the embedded ethics of Judaism itself, divorced from the "redistributionist" theories of Marxist and neo-Marxist adherents. Whereas the Essene sectarians withdrew from what they called "the material wealth of wickedness," Jesus admonished his disciples to pursue dealings out of economic contact with the world at large.